Biodegradable mulching film and preparation method thereof

By using composite technology of starch, cellulose, chitosan and other materials in biodegradable plastic film, and performing heating and plasticization and traction cooling treatment, the existing biodegradable plastic film is solved, and the efficient improvement of the plastic film is achieved to meet the needs of agricultural machinery operations.

CN119552484APending Publication Date: 2025-03-04BEIJING ACADEMY OF AGRICULTURE & FORESTRY SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510096274.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The tensile strength of existing biodegradable plastic film materials is poor and cannot meet the requirements of agricultural machinery operations.

Method used

The composite use of starch, cellulose, chitosan, polylactic acid, polybutylene terephthalate, polymethylethylene carbonate, polyhydroxy fatty acid esters, polyethylene crosslinkers and other materials is used, and the mechanical strength and stability of the mulch film are improved through heating plasticization, extrusion molding, traction and cooling processes.

Benefits of technology

It significantly improves the tensile strength and stability of biodegradable plastic film, can meet the requirements of agricultural machinery operations, and at the same time enhances the toughness and heat resistance of plastic film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552484A_ABST
    Figure CN119552484A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biodegradable mulching films, particularly relates to a biodegradable mulching film and a preparation method thereof, and provides the following scheme aiming at the problem that the existing biodegradable mulching film material is poor in tensile strength due to the physical and chemical properties of the existing biodegradable mulching film material, so that the agricultural machinery operation requirement cannot be met. The invention discloses a degradable plastic film which is prepared from the following raw materials in parts by weight: 20-35 parts of starch, 5-15 parts of cellulose, 5-15 parts of chitosan and 10-30 parts of polylactic acid. The degradable plastic film is prepared from the following components in parts by weight: starch, cellulose, chitosan, polylactic acid, poly (butylene adipate-co-terephthalate), polymethyl ethylene carbonate, polyhydroxyalkanoate, a polyethylene cross-linking agent, ammonium stearate and calcium carbonate. By using the humus concentrated solution, the light stabilizer, the antifogging agent, the antistatic agent, the compatilizer, the polyethylene wax, the phenyl salicylate, the talcum powder, the mica powder and the kaolin, the tensile strength and the stability of the mulching film are effectively improved, so that the agricultural machinery operation requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable mulch films, and in particular to a biodegradable mulch film and a preparation method thereof. Background Art

[0002] Ground film has the functions of heat preservation, moisture retention, soil moisture retention and fertilizer increase, which can greatly increase the yield of crops. The use of ground film is very large, which has made an important contribution to ensuring the safe supply of food and cash crops. It is predicted that in the next 10 years, the use of ground film will increase by about 10%, and the future coverage area is expected to reach 500 million mu, and the amount will reach 2 million tons. However, with the increasing amount of film laying, the treatment of residual ground film in farmland has reached a point of urgency. The fully biodegradable ground film is a new product that can quickly biodegrade in the soil environment and disappear automatically after use. It is considered to be the most likely solution to the "white pollution" of farmland, and has great development potential.

[0003] In the prior art, the physical and chemical properties of the biodegradable mulch material itself result in poor tensile strength, which makes it unable to meet the requirements of agricultural machinery operations. To this end, we propose a biodegradable mulch and a preparation method thereof to solve the above problem. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art that the physical and chemical properties of the biodegradable mulch material itself lead to poor tensile strength, thereby failing to meet the requirements of agricultural machinery operations, and to propose a biodegradable mulch and a preparation method thereof.

[0005] The present application provides a biodegradable mulch film and a preparation method thereof using the following technical solutions: A biodegradable mulch film comprises raw materials, wherein the raw materials comprise the following components in parts by weight: 20-35 parts of starch, 5-15 parts of cellulose, 5-15 parts of chitosan, 10-30 parts of polylactic acid, 80-200 parts of polybutylene adipate terephthalate, 80-200 parts of polymethyl ethylene carbonate, 80-200 parts of polyhydroxyalkanoate, 20-50 parts of polyethylene crosslinking agent, 10-20 parts of ammonium stearate, 10-20 parts of calcium carbonate, 1-6 parts of humus concentrate, 2-10 parts of light stabilizer, 2-10 parts of antifogging agent, 2-10 parts of antistatic agent, 5-15 parts of compatibilizer, 5-15 parts of polyethylene wax, 10-25 parts of phenyl o-hydroxybenzoate, 2-10 parts of talc, 2-10 parts of mica powder and 2-10 parts of kaolin.

[0006] Furthermore, the raw materials include the following components in parts by weight: 15-25 parts of starch, 8-12 parts of cellulose, 8-12 parts of chitosan, 15-20 parts of polylactic acid, 120-150 parts of polybutylene adipate terephthalate, 120-150 parts of polymethyl ethylene carbonate, 120-150 parts of polyhydroxyalkanoate, 30-40 parts of polyethylene crosslinking agent, 12-18 parts of ammonium stearate, 12-18 parts of calcium carbonate, 3-5 parts of humus concentrate, 4-8 parts of light stabilizer, 4-8 parts of antifogging agent, 4-8 parts of antistatic agent, 8-12 parts of compatibilizer, 8-12 parts of polyethylene wax, 15-20 parts of phenyl o-hydroxybenzoate, 4-6 parts of talc, 4-6 parts of mica powder, 4-6 parts of kaolin. 15-20 parts of phenyl benzoate, 4-6 parts of talc, 4-6 parts of mica powder, 4-6 parts of kaolin.

[0007] Furthermore, the raw materials include the following components in parts by weight: 20 parts of starch, 10 parts of cellulose, 10 parts of chitosan, 18 parts of polylactic acid, 135 parts of polybutylene adipate terephthalate, 135 parts of polymethyl ethylene carbonate, 135 parts of polyhydroxyalkanoate, 35 parts of polyethylene crosslinker, 15 parts of ammonium stearate, 15 parts of calcium carbonate, 4 parts of humus concentrate, 6 parts of light stabilizer, 6 parts of antifogging agent, 6 parts of antistatic agent, 10 parts of compatibilizer, 10 parts of polyethylene wax, 18 parts of phenyl o-hydroxybenzoate, 5 parts of talc, 5 parts of mica powder, and 5 parts of kaolin.

[0008] The present invention also provides a method for preparing a biodegradable mulch film, comprising the following steps: S1: Select raw materials and pre-treat them; S2: mixing the pretreated raw materials and plasticizing the mixed raw materials; S3: Extruding the plasticized material into a mold and monitoring the molding temperature; S4: pulling and cooling the extruded ground film, and monitoring the pulling speed; S5: rolling and packaging the ground film after cooling and pulling treatment; S6: Conduct quality inspection on the produced biodegradable mulch film machines.

[0009] Furthermore, in S1, starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are dried by a drying mechanism, and the dried raw materials are crushed by a crushing mechanism, and the crushed raw materials are screened by a screening mechanism.

[0010] Furthermore, in S2, the pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinking agent, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, the materials are stirred and mixed by the mixing mechanism, and then added. The thermal mechanism heats and plasticizes the mixed material. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 170-230°C.

[0011] Furthermore, in S3, the plasticized mixed material is extruded and molded by an extruder to obtain a ground film, and the temperature of the extruder is monitored in real time by a monitoring device. The temperature of the first stage of the extruder is 100-120°C, the temperature of the second stage is 120-140°C, the temperature of the third stage is 130-150°C, and the temperature of the die head is 150-170°C.

[0012] Furthermore, in S4, the extruded ground film is towed by a traction machine at a traction speed of 1-5 km / h, and the ground film is cooled by a cooling mechanism using a water cooling circulation system, and the traction speed is monitored in real time by a monitoring device.

[0013] Furthermore, in S5, the ground film after the cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine.

[0014] Furthermore, in S6, the packaged ground film is selectively sampled by the selection mechanism, and the ground film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by the detection mechanism.

[0015] Cellulose is a macromolecular polysaccharide composed of glucose. It is insoluble in water and general organic solvents. It is the main component of plant cell walls. Cellulose is the most widely distributed and abundant polysaccharide in nature, accounting for more than 50% of the carbon content in the plant kingdom. The cellulose content of cotton is close to 100%, which is the purest natural source of cellulose. In general wood, cellulose accounts for 40-50%, and there are 10-30% hemicellulose and 20-30% lignin. Cellulose is the main structural component of plant cell walls, usually combined with hemicellulose, pectin and lignin. The way and degree of combination have a great influence on the texture of plant-based foods. The change in texture of plants during maturity and ripening is caused by changes in pectin substances. Cellulase does not exist in the human digestive tract. Cellulose is an important dietary fiber. Chitosan is the product of N-deacetylation of chitin. Chitin (chitin), chitosan and cellulose have similar chemical structures. Cellulose has a hydroxyl group at the C2 position, while chitin and chitosan are replaced by an acetylamino group and an amino group at the C2 position respectively. Chitin and chitosan have many unique properties such as biodegradability, cell affinity and biological effects. In particular, chitosan containing free amino groups is the only alkaline polysaccharide among natural polysaccharides. The amino group in the chitosan molecular structure is more reactive than the acetylamino group in the chitin molecule, which makes the polysaccharide have excellent biological functions and can undergo chemical modification reactions. Therefore, chitosan is considered to be a functional biomaterial with greater application potential than cellulose. Chitosan is a product of the natural polysaccharide chitin with partial acetyl removal. It has multiple physiological functions such as biodegradability, biocompatibility, non-toxicity, antibacterial, anti-cancer, lipid-lowering, and immune enhancement. It is widely used in food additives, textiles, agriculture, environmental protection, beauty and health care, cosmetics, antibacterial agents, medical fibers, medical dressings, artificial tissue materials, drug sustained-release materials, gene transduction vectors, biomedical fields, medical absorbable materials, tissue engineering carrier materials, medical and drug development, and many other fields and other daily chemical industries; Mica powder is a non-metallic mineral containing a variety of components, mainly SiO2, which is generally about 49%, and Al2O3, which is about 30%. Mica powder has good elasticity, toughness, insulation, high temperature resistance, acid and alkali resistance, corrosion resistance, strong adhesion and other characteristics, and is an excellent additive. It is widely used in electrical appliances, welding rods, rubber, plastics, papermaking, paints, coatings, pigments, ceramics, cosmetics, new building materials and other industries. It has a wide range of uses. With the continuous development of science and technology, people have opened up new application fields; Kaolin, theoretical chemical formula: Al2[(OH)4 / Si2O5], is a non-metallic mineral, a clay and clay rock mainly composed of kaolinite clay minerals. Because it is white and fine, it is also called dolomite, named after Gaoling Village in Jingdezhen, Jiangxi Province. Its pure kaolin is white, fine, soft soil-like, with good plasticity and refractoriness and other physical and chemical properties. Its mineral composition is mainly composed of kaolinite, halloysite, hydromica, illite, montmorillonite, quartz, feldspar and other minerals. Kaolin is widely used, mainly in papermaking, ceramics and refractory materials, secondly in coatings, rubber fillers, enamel glazes and white cement raw materials, and a small amount is used in plastics, paints, pigments, grinding wheels, pencils, daily cosmetics, soaps, pesticides, medicines, textiles, petroleum, chemicals, building materials, national defense and other industrial sectors.

[0016] In summary, the present application includes at least one of the following beneficial technical effects: 1. In this scheme, polybutylene adipate terephthalate and polylactic acid are used in combination to enhance the toughness and heat resistance of the mulch film. Polyhydroxyalkanoate has good biocompatibility and biodegradability, which improves the overall performance of the mulch film. 2. The light stabilizer, antifogging agent and antistatic agent in this scheme are used to improve the light stability, antifogging and antistatic properties of the ground film. The compatibilizer can enhance the compatibility in the formula system, assist in the molding of the granular material, and improve the toughness and strength of the ground film; 3. In this scheme, starch, cellulose, and chitosan can improve the mechanical strength of the ground film, and talcum powder, mica powder, and kaolin used as fillers or reinforcing agents can improve the rigidity and wear resistance of the ground film while reducing costs.

[0017] The present invention effectively improves the tensile strength and stability of the ground film by using starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, polyhydroxyalkanoate, polyethylene crosslinking agent, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talc, mica powder and kaolin, thereby being able to meet the requirements of agricultural machinery operations. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart of a method for preparing a biodegradable mulch film. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0020] Embodiment 1 Reference Figure 1 A biodegradable mulch film includes raw materials, which include the following components in parts by weight: 20 parts of starch, 5 parts of cellulose, 5 parts of chitosan, 10 parts of polylactic acid, 80 parts of polybutylene adipate terephthalate, 80 parts of polymethyl ethylene carbonate, 80 parts of polyhydroxyalkanoate, 20 parts of polyethylene cross-linking agent, 10 parts of ammonium stearate, 10 parts of calcium carbonate, 1 part of humus concentrate, 2 parts of light stabilizer, 2 parts of antifogging agent, 2 parts of antistatic agent, 5 parts of compatibilizer, 5 parts of polyethylene wax, 10 parts of phenyl o-hydroxybenzoate, 2 parts of talc, 2 parts of mica powder, and 2 parts of kaolin.

[0021] This embodiment also proposes a method for preparing a biodegradable mulch film, comprising the following steps: S1: Drying starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate by a drying mechanism, crushing the dried raw materials by a crushing mechanism, and screening the crushed raw materials by a screening mechanism; S2: The pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinker, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, and the materials are stirred and mixed by a mixing mechanism, and heated by a heating mechanism. The mixed material is heated and plasticized. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 170°C. S3: Extruding the plasticized mixed material through an extruder to obtain a ground film, and monitoring the temperature of the extruder in real time through a monitoring device. The first stage temperature of the extruder is 100°C, the second stage temperature is 120°C, the third stage temperature is 130°C, and the die head temperature is 150°C; S4: The extruded ground film is towed by a traction machine at a traction speed of 1 km / h. The ground film is cooled by a cooling mechanism, which adopts a water cooling circulation system. The traction speed is monitored in real time by a monitoring device. S5: The ground film after cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine; S6: The packaged mulch film is selectively inspected by a selection agency, and the mulch film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by a testing agency.

[0022] Embodiment 2 Reference Figure 1 A biodegradable mulch film includes raw materials, which include the following components in parts by weight: 24 parts of starch, 8 parts of cellulose, 8 parts of chitosan, 15 parts of polylactic acid, 120 parts of polybutylene adipate terephthalate, 120 parts of polymethyl ethylene carbonate, 120 parts of polyhydroxyalkanoate, 25 parts of polyethylene cross-linking agent, 14 parts of ammonium stearate, 14 parts of calcium carbonate, 2 parts of humus concentrate, 4 parts of light stabilizer, 4 parts of antifogging agent, 4 parts of antistatic agent, 8 parts of compatibilizer, 8 parts of polyethylene wax, 14 parts of phenyl o-hydroxybenzoate, 4 parts of talc, 4 parts of mica powder, and 4 parts of kaolin.

[0023] This embodiment also proposes a method for preparing a biodegradable mulch film, comprising the following steps: S1: Drying starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate by a drying mechanism, crushing the dried raw materials by a crushing mechanism, and screening the crushed raw materials by a screening mechanism; S2: The pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinker, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, and the materials are stirred and mixed by a mixing mechanism, and heated by a heating mechanism. The mixed material is heated and plasticized. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 180°C. S3: Extruding the plasticized mixed material through an extruder to obtain a ground film, and monitoring the temperature of the extruder in real time through a monitoring device. The temperature of the first stage of the extruder is 105°C, the temperature of the second stage is 125°C, the temperature of the third stage is 135°C, and the temperature of the die head is 155°C; S4: The extruded ground film is towed by a traction machine at a traction speed of 2 km / h. The ground film is cooled by a cooling mechanism, which adopts a water cooling circulation system. The traction speed is monitored in real time by a monitoring device. S5: The ground film after cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine; S6: The packaged mulch film is selectively inspected by a selection agency, and the mulch film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by a testing agency.

[0024] Embodiment 3 Reference Figure 1 A biodegradable mulch film includes raw materials, which include the following components in parts by weight: 28 parts of starch, 12 parts of cellulose, 12 parts of chitosan, 20 parts of polylactic acid, 150 parts of polybutylene adipate terephthalate, 150 parts of polymethyl ethylene carbonate, 150 parts of polyhydroxyalkanoate, 35 parts of polyethylene cross-linking agent, 16 parts of ammonium stearate, 16 parts of calcium carbonate, 3 parts of humus concentrate, 6 parts of light stabilizer, 6 parts of antifogging agent, 6 parts of antistatic agent, 12 parts of compatibilizer, 12 parts of polyethylene wax, 18 parts of phenyl o-hydroxybenzoate, 6 parts of talc, 6 parts of mica powder, and 6 parts of kaolin.

[0025] This embodiment also proposes a method for preparing a biodegradable mulch film, comprising the following steps: S1: Drying starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate by a drying mechanism, crushing the dried raw materials by a crushing mechanism, and screening the crushed raw materials by a screening mechanism; S2: The pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinker, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, and the materials are stirred and mixed by a mixing mechanism, and heated by a heating mechanism. The mixed material is heated and plasticized. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 200°C. S3: Extruding the plasticized mixed material through an extruder to obtain a ground film, and monitoring the temperature of the extruder in real time through a monitoring device. The temperature of the first stage of the extruder is 110°C, the temperature of the second stage is 130°C, the temperature of the third stage is 140°C, and the temperature of the die head is 160°C; S4: The extruded ground film is towed by a traction machine at a traction speed of 3 km / h. The ground film is cooled by a cooling mechanism, which adopts a water cooling circulation system. The traction speed is monitored in real time by a monitoring device. S5: The ground film after cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine; S6: The packaged mulch film is selectively inspected by a selection agency, and the mulch film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by a testing agency.

[0026] Embodiment 4 Reference Figure 1 A biodegradable mulch film includes raw materials, which include the following components in parts by weight: 32 parts of starch, 14 parts of cellulose, 14 parts of chitosan, 25 parts of polylactic acid, 180 parts of polybutylene adipate terephthalate, 180 parts of polymethyl ethylene carbonate, 180 parts of polyhydroxyalkanoate, 45 parts of polyethylene cross-linking agent, 18 parts of ammonium stearate, 18 parts of calcium carbonate, 5 parts of humus concentrate, 8 parts of light stabilizer, 8 parts of antifogging agent, 8 parts of antistatic agent, 14 parts of compatibilizer, 14 parts of polyethylene wax, 22 parts of phenyl o-hydroxybenzoate, 8 parts of talc, 8 parts of mica powder, and 8 parts of kaolin.

[0027] This embodiment also proposes a method for preparing a biodegradable mulch film, comprising the following steps: S1: Drying starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate by a drying mechanism, crushing the dried raw materials by a crushing mechanism, and screening the crushed raw materials by a screening mechanism; S2: The pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinker, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, and the materials are stirred and mixed by a mixing mechanism, and heated by a heating mechanism. The mixed material is heated and plasticized. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 220°C. S3: The plasticized mixed material is extruded through an extruder to obtain a ground film. The temperature of the extruder is monitored in real time through a monitoring device. The temperature of the first stage of the extruder is 115°C, the temperature of the second stage is 135°C, the temperature of the third stage is 145°C, and the temperature of the die head is 165°C. S4: The extruded ground film is towed by a traction machine at a traction speed of 4 km / h. The ground film is cooled by a cooling mechanism, which adopts a water cooling circulation system. The traction speed is monitored in real time by a monitoring device. S5: The ground film after cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine; S6: The packaged mulch film is selectively inspected by a selection agency, and the mulch film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by a testing agency.

[0028] Embodiment 5 Reference Figure 1 A biodegradable mulch film includes raw materials, which include the following components in parts by weight: 35 parts of starch, 15 parts of cellulose, 15 parts of chitosan, 30 parts of polylactic acid, 200 parts of polybutylene adipate terephthalate, 200 parts of polymethyl ethylene carbonate, 200 parts of polyhydroxyalkanoate, 50 parts of polyethylene cross-linking agent, 20 parts of ammonium stearate, 20 parts of calcium carbonate, 6 parts of humus concentrate, 10 parts of light stabilizer, 10 parts of antifogging agent, 10 parts of antistatic agent, 15 parts of compatibilizer, 15 parts of polyethylene wax, 25 parts of phenyl o-hydroxybenzoate, 10 parts of talc, 10 parts of mica powder, and 10 parts of kaolin.

[0029] This embodiment also proposes a method for preparing a biodegradable mulch film, comprising the following steps: S1: Drying starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate by a drying mechanism, crushing the dried raw materials by a crushing mechanism, and screening the crushed raw materials by a screening mechanism; S2: The pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinker, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, and the materials are stirred and mixed by a mixing mechanism, and heated by a heating mechanism. The mixed material is heated and plasticized. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 230°C. S3: Extruding the plasticized mixed material through an extruder to obtain a ground film, and monitoring the temperature of the extruder in real time through a monitoring device. The temperature of the first stage of the extruder is 120°C, the temperature of the second stage is 140°C, the temperature of the third stage is 150°C, and the temperature of the die head is 170°C; S4: The extruded ground film is towed by a traction machine at a traction speed of 5 km / h. The ground film is cooled by a cooling mechanism, which adopts a water cooling circulation system. The traction speed is monitored in real time by a monitoring device. S5: The ground film after cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine; S6: The packaged mulch film is selectively inspected by a selection agency, and the mulch film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by a testing agency.

[0030] Experimental example By comparing the preparation schemes of the biodegradable mulch proposed in Examples 1 to 5 with the conventional preparation schemes of the biodegradable mulch, the experimental data are as follows:

[0031] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A biodegradable mulch film, comprising raw materials, characterized in that: The raw materials include the following components in parts by weight: 20-35 parts of starch, 5-15 parts of cellulose, 5-15 parts of chitosan, 10-30 parts of polylactic acid, 80-200 parts of polybutylene adipate terephthalate, 80-200 parts of polymethyl ethylene carbonate, 80-200 parts of polyhydroxyalkanoate, 20-50 parts of polyethylene crosslinking agent, 10-20 parts of ammonium stearate, 10-20 parts of calcium carbonate, 1-6 parts of humus concentrate, 2-10 parts of light stabilizer, 2-10 parts of antifogging agent, 2-10 parts of antistatic agent, 5-15 parts of compatibilizer, 5-15 parts of polyethylene wax, 10-25 parts of phenyl o-hydroxybenzoate, 2-10 parts of talc, 2-10 parts of mica powder and 2-10 parts of kaolin.

2. The biodegradable mulch film according to claim 1, characterized in that: The raw materials include the following components in parts by weight: 15-25 parts of starch, 8-12 parts of cellulose, 8-12 parts of chitosan, 15-20 parts of polylactic acid, 120-150 parts of polybutylene adipate terephthalate, 120-150 parts of polymethyl ethylene carbonate, 120-150 parts of polyhydroxyalkanoate, 30-40 parts of polyethylene crosslinking agent, 12-18 parts of ammonium stearate, 12-18 parts of calcium carbonate, 3-5 parts of humus concentrate, 4-8 parts of light stabilizer, 4-8 parts of antifogging agent, 4-8 parts of antistatic agent, 8-12 parts of compatibilizer, 8-12 parts of polyethylene wax, 15-20 parts of phenyl o-hydroxybenzoate, 4-6 parts of talc, 4-6 parts of mica powder and 4-6 parts of kaolin.

3. A biodegradable mulch film according to claim 2, characterized in that: The raw materials include the following components in parts by weight: 20 parts of starch, 10 parts of cellulose, 10 parts of chitosan, 18 parts of polylactic acid, 135 parts of polybutylene adipate terephthalate, 135 parts of polymethyl ethylene carbonate, 135 parts of polyhydroxyalkanoate, 35 parts of polyethylene crosslinking agent, 15 parts of ammonium stearate, 15 parts of calcium carbonate, 4 parts of humus concentrate, 6 parts of light stabilizer, 6 parts of antifogging agent, 6 parts of antistatic agent, 10 parts of compatibilizer, 10 parts of polyethylene wax, 18 parts of phenyl o-hydroxybenzoate, 5 parts of talc, 5 parts of mica powder, and 5 parts of kaolin.

4. A method for preparing a biodegradable mulch film, wherein the biodegradable mulch film is a biodegradable mulch film according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Select raw materials and pre-treat them; S2: mixing the pretreated raw materials and plasticizing the mixed raw materials; S3: Extruding the plasticized material into a mold and monitoring the molding temperature; S4: pulling and cooling the extruded ground film, and monitoring the pulling speed; S5: rolling and packaging the ground film after cooling and pulling treatment; S6: Conduct quality inspection on the produced biodegradable mulch film machines.

5. The method for preparing a biodegradable mulch film according to claim 4, characterized in that: In S1, starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are dried by a drying mechanism, and the dried raw materials are crushed by a crushing mechanism, and the crushed raw materials are screened by a screening mechanism.

6. The method for preparing a biodegradable mulch film according to claim 5, characterized in that: In S2, the pretreated starch, cellulose, chitosan, polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate, and polyhydroxyalkanoate are mixed by a mixing mechanism, and polyethylene crosslinking agent, ammonium stearate, calcium carbonate, humus concentrate, light stabilizer, antifogging agent, antistatic agent, compatibilizer, polyethylene wax, phenyl o-hydroxybenzoate, talcum powder, mica powder, and kaolin are added to the mixture by an adding mechanism, the materials are stirred and mixed by the mixing mechanism, and the mixture is heated by a heating mechanism. The mixed material is heated and plasticized. Starch, cellulose and chitosan are degraded when heated. Polylactic acid, polybutylene adipate terephthalate, polymethyl ethylene carbonate and polyhydroxyalkanoate are melted when heated to produce small molecular segments. Ammonium stearate is decomposed when heated to produce stearic acid and ammonia. Calcium carbonate is decomposed when heated to produce calcium oxide and carbon dioxide. Light stabilizers, antifogging agents, antistatic agents, compatibilizers, polyethylene wax and phenyl o-hydroxybenzoate are used to improve the performance of the material. The heating temperature is 170-230°C.

7. The method for preparing a biodegradable mulch film according to claim 6, characterized in that: In S3, the plasticized mixed material is extruded and molded by an extruder to obtain a ground film, and the temperature of the extruder is monitored in real time by a monitoring device. The temperature of the first stage of the extruder is 100-120°C, the temperature of the second stage is 120-140°C, the temperature of the third stage is 130-150°C, and the temperature of the die head is 150-170°C.

8. The method for preparing a biodegradable mulch film according to claim 7, characterized in that: In S4, the extruded ground film is towed by a traction machine at a traction speed of 1-5 km / h, and the ground film is cooled by a cooling mechanism using a water cooling circulation system. The traction speed is monitored in real time by a monitoring device.

9. The method for preparing a biodegradable mulch film according to claim 8, characterized in that: In S5, the ground film after the cooling and pulling treatment is rolled up by a rolling device to form a roll, and the rolled ground film is packaged by a packaging machine.

10. The method for preparing a biodegradable mulch film according to claim 9, characterized in that: In S6, the packaged ground film is selectively inspected by the selection mechanism, and the ground film is subjected to appearance inspection, thickness measurement, tensile strength test and degradation performance test by the detection mechanism.

Citation Information

Cited By

  • Degradable composite mulching film material as well as preparation method and application thereof

    CN121495309A